Examination of requirements of labour market, connected with competencies of agrienvironmental engineers and nature protection engineers - Mocsáriné Fricz, Julianna (Acta Agraria Debreceniensis, 2009)
The most important goal of firms is to supply demand of their economic partners. To make it successfully, highly qualified human resource is needed. The quality of human resource is determined not only by qualification, command of a language, professional experience, practise, but extant competencies that can also be developped. To choose the expectant employee, it is not enough to have intelligence and proficiency. It is also decesive to examine particular competencies. All of these will define the employee’s achievement that can be the right way to the success ofthe enterprise. It is need to make the cooperation between higher education institutions and employers closer. As a result of this, employers can know theirs ways about possibilities of the new higher educational training system. They can use professional knowledge, competencies of the Bologna system’s graduates at different pointsof the economic life. The higher education institutions can revise their training systems considering requirements of labour market. According to these requirements, they can form syllabus in order to train auspicious experts.